SUN PROTECTOR FACTOR (SPF) IN VITRO AND THE PHYSICAL STABILITY OF O/W CREAM OPTIMAL FORMULA FROM THE PARTITION PRODUCT OF MAHKOTA DEWA LEAVES [Phaleria macrocarpa (Scheff) Boerl] - Zulkarnain, Abdul Karim; Marchaban, Marchaban; Wahyuono, Subagus; Susidarti, Ratna Asmah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The leaves Mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) contains a benzophenoic glycoside (Phalerin) which is active for sun screen. Some formula and designed on the Simplex Lattice Design (SLD) method then its physical characteristics were investigated. The physical characteristics will be used to determine the optimum formula. In present study, the optimum formulation was evaluated to determine chemical stability and the in vitro SPF. The doses of partition product of P. macrocarpa was used 6%. The optimal formulation cream was determined by SLD version 9.0.1 with variety of Cetyl alcohol, mineral oil, and Tween 80. The difference of physical characteristics between experimental and software was analyzed using T-test, P= 95 %. The physical stability and in vitro SPF of the optimum formula was observed. he study exhibits that the combination of cetyl alchodol 9,71%, mineral oil 29%, and tween 80 3,29% was the optimum formula of o/w cream with the desirability test 0,924. The T-test result test shows that there is no significant difference (p>0.05) on physical characteristics between experimental and software prediction. During the storage, the viscosity, spread ability, adhesive ability, separation volume ratio of cream was relatively stable however the stability started to decline on the week IV in the extreme temperature. The SPF of the cream of the CFR, CPHR and CBZP partition were 21,32; 33,12 and 42,49, respectively.Keywords: Mahkota dewa, cream, optimum, SPF